IMPLICATIONS OF ECONOMIC EDUCATION AND RATIONALITY OF ISLAMIC ECONOMIC LIFE STYLE Salik - Nuraini, Emi; Priyantini, Merlyawati (http://jagadalimussirry.com/, 2018)
The purpose of this study was: (1) to analyze how economic education in the family environment, economic rationality, and salik lifestyle ; (2 ) to analyze how economic education in the family environment and economic rationality have implications for the salik lifestyle. The method in this research used quantitative descriptive. The results showed that (1) economic education in the family environment and the economic rationality of the salik were high, and the salik lifestyle tended to be a simple lifestyle, (2) the salik are educated by their parents in managing finances and controlling expenses, so they are trained to be simple individuals. Likewise, the economic rationality of the salik is inseparable from Islamic rules, which always insert the intention to worship Allah and not be Islamic in every economic activity.